Complications and Their Risk Factors following Hip Fracture Surgery - Keng Soon Poh; K Lingaraj (Journal of Orthopaedic Surgery, 2013)
Purpose. To evaluate various postoperative complications and their risk factors in hip fracture patients. Methods. 207 female and 87 male consecutive patients (mean age, 78.1 years) who underwent surgical (n=242) or conservative (n=52) treatment for closed fractures of the femoral neck (n=157) or peritrochanter (n=137) were prospectively studied. The types of complication and outcome were recorded. The comorbidity status of the patients was categorised based on the American Society of Anesthesiologists (ASA) classification. Complications and their associations with various risk factors and mortality were analysed. Results. For all patients, the mean length of hospitalisation was 14.6 days. For the 242 patients who underwent surgical treatment after a mean of 3.6 days, 56.8% of them had at least one complication. Acute urinary retention (39.3%) and urinary tract infection (24.0%) were most common. Patients with ASA grade III or higher had 2.3 fold higher risk of developing complications than those with lower-grade comorbidity, whereas patients with delayed operation (>48 hours after presentation) had 1.8 fold higher risk of developing complications than those without delayed operation. Four patients died in hospital: 2 from myocardial infarction and 2 from upper gastrointestinal bleeding. Conclusion. Complications after hip fracture surgery were common. Advanced age, high ASA status, and delay in surgery were associated with higher complication rates. Operations should be performed on medically fit patients as early as possible.